No Better Moment to Score a Goal than Just Before Half Time? A Soccer Myth Statistically Tested - Stijn Baert; Simon Amez (Institute for the Study of Labor (IZA), 2016)
We test the soccer myth suggesting that a particularly good moment to score a goal is just before half time. To this end, rich data on 1,179 games played in the UEFA Champions League and UEFA Europa League are analysed. In contrast to the myth, we find that, conditional on the goal difference and other game characteristics at half time, the final goal difference at the advantage of the home team is 0.520 goals lower in case of a goal just before half time by this team. We show that this finding relates to this team's lower probability of scoring a goal during the second half.
Keywords: L83; J44; Z00; 330; soccer; sports; goal scoring; fixed effects regression models